Effect of Single Dose Betamethasone Administration in Pregnancy on Maternal and Newborn Parameters - Gaur, Komal (J Clin Diagn Res, 2017)
INTRODUCTION: Antenatal corticosteroids play an important role in preventing Respiratory Distress Syndrome (RDS) but benefits related to time between corticosteroid administration and delivery need to be explored. AIM: To observe the effect of betamethasone administration in pregnant women at risk of preterm delivery and on foetal parameters, in terms of development of RDS. MATERIALS AND METHODS: It was a prospective observational study on pregnant women at risk of preterm delivery who were administered a single dose 24 mg injection betamethasone. Outcome of 111 newborns of enrolled mothers was observed in terms of respiratory distress, Downe’s and Silverman Anderson score, need of NICU admission and ventilation. Paired t-test was used to compare means of maternal parameters before and after betamethasone. Independent sample t-test for comparison of scores for respiratory distress in neonates was used. RESULTS: There was a significant decrease in maternal haematological parameters like mean Red Blood Cell (RBC) and mean Platelet Count (PC) whereas increase in mean Total leucocyte Count (TC) after betamethasone administration. Out of 111 newborn babies, 71 were born within 24 hours and rest were born after 24 hours of betamethasone administration. Twelve out of 71 newborns who were born within 24 hours of betamethasone administration, developed RDS. Mean Downe’s score and mean Silverman Anderson score in neonates born within 24 hours of injection administration were significantly higher than those born after 24 hours. CONCLUSION: Betamethasone administration affects the haematological parameters in mothers in antenatal period nearing term. A minimum of 24 hours have to elapse between corticosteroid administration and delivery of the preterm for benefits to occur.